Emodin Retarded Renal Fibrosis Through Regulating HGF and TGFβ–Smad Signaling Pathway - Yang F; Deng L; Li J; Chen M; Liu Y; Hu Y; Zhong W (Dove Medical Press, 2020)
Fan Yang,1 Lu Deng,2 JinPeng Li,3 MuHu Chen,1 Ying Liu,1 YingChun Hu,1 Wu Zhong1 1Department of Emergency Medicine, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan 646000, People’s Republic of China; 2Department of Thyroid Surgery, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan 646000, People’s Republic of China; 3Department of Thyroid and Breast Surgery, Wuhan University Zhongnan Hospital, Wuhan, Hubei 430071, People’s Republic of ChinaCorrespondence: Wu Zhong Department of Emergency MedicineAffiliated Hospital of Southwest Medical University, 25 Taiping Street, Luzhou, Sichuan 646000, People’s Republic of ChinaEmail zhongwu3987@126.comBackground: Renal fibrosis is a frequently occurring type of chronic kidney disease that can cause end-stage renal disease. It has been verified that emodin or HGF can inhibit the development of renal fibrosis. However, the antifibrotic effect of emodin in combination with HGF remains unclear.Methods: Cell viability was detected with CCK8. Gene and protein expression in HK2 cells was detected by qRT-PCR and Western blot, respectively. Moreover, a unilateral ureteral obstruction–induced mouse model of renal fibrosis was established for investigating the antifibrotic effect of emodin in combination with HGF in vivo.Results: HGF notably increased the expression of collagen II in TGFβ-treated HK2 cells. In addition, HGF-induced increase in collagen II expression was further enhanced by emodin. In contrast, fibronectin, αSMA and Smad2 expression in TGFβ-stimulated HK2 cells was significantly inhibited by HGF and further decreased by combination treatment (emodin plus HGF). Moreover, we found that combination treatment exhibited better antifibrotic effects compared with emodin or HGF in vivo.Conclusion: These data demonstrated that emodin plus HGF exhibited better antifibrotic effects compared with emodin or HGF. As such, emodin in combination with HGF may serve as a new possibilty for treatment of renal fibrosis.Keywords: fibrosis, combination, emodin, TGFβ